Autologous Adoptive T-cell Therapy for Recurrent or Drug-resistant Cytomegalovirus Complications in Solid Organ Transplant Recipients: A Single-arm Open-label Phase I Clinical Trial. (5th July 2018) - Smith, Corey; Beagley, Leone; Rehan, Sweera; Neller, Michelle A; Crooks, Pauline; Solomon, Matthew; Holmes-Liew, Chien-Li; Holmes, Mark; McKenzie, Scott C; Hopkins, Peter; Campbell, Scott; Francis, Ross S; et al.
Abstract : Autologous T-cell therapy in solid organ transplant recipients with recurrent or drug-resistant CMV-associated complications is safe and may provide clinical benefit, especially when standard therapies are not effective or are contraindicated. Abstract: Background: Opportunistic infections including cytomegalovirus (CMV) are a major cause of morbidity and mortality in solid organ transplant (SOT) recipients. The recurrent and protracted use of antiviral drugs with eventual emergence of drug resistance represents a significant constraint to therapy. Although adoptive T-cell therapy has been successfully used in hematopoietic stem cell transplant recipients, its extension to the SOT setting poses a considerable challenge because of the inhibitory effects of immunosuppressive drugs on the virus-specific T-cell response in vivo and the perceived risk of graft rejection. Methods: In this prospective study, 22 SOT recipients (13 renal and 8 lung and 1 heart transplants) with recurrent or ganciclovir-resistant CMV infection were recruited, and 13 of them were treated with in vitro–expanded autologous CMV-specific T cells. These patients were monitored for safety, clinical symptoms, and immune reconstitution. Results: Autologous CMV-specific T-cell manufacture was attempted for 21 patients, and was successful in 20. The use of this adoptive immunotherapy was associated with no therapy-related serious adverse events. Eleven (84%) of the 13 treated patients showed improvement in symptoms, including complete resolution or reduction in DNAemia and CMV-associated end-organ disease and/or the cessation or reduced use of antiviral drugs. Furthermore, four of these patients showed coincident increased frequency of CMV-specific T cells in peripheral blood after completion of T-cell therapy. Conclusions: The data presented here demonstrate for the first time the clinical safety of CMV-specific adoptive T-cell therapy and its potential therapeutic benefit for SOT recipients with recurrent and/or drug-resistant CMV infection or disease. Clinical Trials Registration: ACTRN12613000981729.